2014
DOI: 10.1080/15487768.2014.903876
|View full text |Cite
|
Sign up to set email alerts
|

Peer Career Implications of an Academic Credential: Report from the Field

Abstract: Thousands of peer workers are trained, certified, and employed throughout the United States. Although the importance of education in behavioral health career development is well documented, almost no current literature is available on academic peer career development. This article reports on peer and nonpeer educational and employment outcomes following completion of a credit-bearing community college mental health certificate program. Implications and recommendations for peer workforce development are identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…; Hurley et al . ; Wolf ). As a result, the way peer workers are employed and included within multidisciplinary service environments is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…; Hurley et al . ; Wolf ). As a result, the way peer workers are employed and included within multidisciplinary service environments is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven papers that addressed employment outcomes, six indicated an increase in employment rates (in any capacity) related to the mental health system at both follow-up (Franke et al, 2010;Gammonley & Luken, 2001;Hegedüs et al, 2016) and post-training periods; Hegedüs et al, 2021;Rapp et al, 2008;Wolf, 2014). One found that more completers were employed in a related field or in accredited settings compared to non-completers (Horwitz et al, 2020).…”
Section: Post-training Employmentmentioning
confidence: 99%
“…Strategies include the need for specific policies and practice that promote role clarity (Jacobson et al . 2012), the value of training and qualifications within the lived experience workforce (Wolf 2014), and specific lived experience supervision (Davis 2015).…”
Section: Reasons For the Growth In The Lived Experience Workforcementioning
confidence: 99%